Minimal Control of Constrained, Partially Controllable & Observable Linear Systems⁎This work was sponsored by the German Federal Ministry of Education and Research in project AlgoRes, grant no. 01jS18066A. It has been performed in the context of the LOEWE center emergenCITY. Issue 2 (2020) - Mora, Edwin; Steinke, Florian
Abstract: We aim at developing control strategies for constrained linear systems without requiring full system controllability and observability. Given a fixed, potentially small set of actuators and sensors, we first design a static affine-linear output feedback controller that guarantees both the asymptotic stability of the closed-loop system and the adherence of the steady state to a set of linear inequality constraints in the presence of interval-bounded, constant inputs. Subsequently, the derived method is used to find the minimum number of actuators and sensors with which one can fulfill such partial controllability and observability requirements. The approach is applied to electrical power networks modeled as a set of linearly coupled oscillators.